2017
DOI: 10.1007/jhep12(2017)121
|View full text |Cite
|
Sign up to set email alerts
|

On avoiding Ostrogradski instabilities within Asymptotic Safety

Abstract: We study the renormalization group flow of gravity coupled to scalar matter using functional renormalization group techniques. The novel feature is the inclusion of higher-derivative terms in the scalar propagator. Such terms give rise to Ostrogradski ghosts which signal an instability of the system and are therefore dangerous for the consistency of the theory. Since it is expected that such terms are generated dynamically by the renormalization group flow they provide a potential threat when constructing a th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 166 publications
(260 reference statements)
0
52
0
Order By: Relevance
“…This indicates that our analysis provides the first study of the gravity-matter fixed point identified in [12,31,83,100] at the level of self-consistent form factors. Comparing the critical exponents (112) and (113) furthermore suggests that the properties of the fixed point are essentially determined by the gravitational contributions [100].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This indicates that our analysis provides the first study of the gravity-matter fixed point identified in [12,31,83,100] at the level of self-consistent form factors. Comparing the critical exponents (112) and (113) furthermore suggests that the properties of the fixed point are essentially determined by the gravitational contributions [100].…”
Section: Resultsmentioning
confidence: 60%
“…reference η s * ∆ [12] −0.361 - [100] 0 - [31] −0.771this work −0.176 1.051 of the differential operators leads to surface terms in Γ k . Thus G k=0 and Λ k=0 are numbers which are independent of the external momenta in a scattering process.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of gravity, higher derivative theories have been studied as modified theories in their own right or as the expected result of renormalization. Under certain conditions, instabilities associated with higher derivative terms can be avoided in renormalization group flows to a nontrivial fixed point [4]. Instabilities can alternatively be avoided by constraints [5] or complexification [6], where the physical relevance of complex theories is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…The main issue with this theory is the presence of ghosts in the perturbative spectrum. Over time, several ways out have been suggested [18][19][20][21], and more recently [22][23][24][25][26][27][28], but this point remains unsettled, for the time being.…”
Section: Introductionmentioning
confidence: 99%